A multi-scenario factorial analysis and multi-regional input-output model for analyzing CO2 emission reduction path in Jing-Jin-Ji region. (1st June 2021) - Wang, P.P.; Li, Y.P.; Huang, G.H.; Wang, S.G.; Suo, C.; Ma, Y.
Abstract: In this study, a multi-scenario factorial analysis and multi-regional input-output (MFA-MRIO) model is developed, which is capable of evaluating carbon dioxide (CO2 ) emission and simulating CO2 emission reduction path, as well as disclosing individual and interactive effects of multi-factor, multi-sector and multi-city for urban agglomeration. A case study of Jing-Jin-Ji region that is one of the most strategic core regions for China's economic development is conducted to prove the applicability of the MFA-MRIO model. Multiple scenarios based on direct CO2 reduction and final demand mitigation on various industries are examined. The major findings are: (i) for the whole region in the future, metallurgical industry, electric heating industry, and transportation would be the main CO2 emission sectors; (ii) among all CO2 emission transfers, CO2 flow from Hebei to Beijing would be the highest, especially for metallurgical industry; (iii) for the whole region in the future, the annual growth rate of CO2 emission from the tertiary industry would be higher than that of the secondary industry; (iv) with a high GDP growth rate, loose direct CO2 reduction policy on sectors would also achieve effective CO2 mitigation; (v) with a high GDP growth rate, appropriate final demand reduction policy on high-carbon industries in Tianjin and Hebei would have a positive effect on carbon intensity reduction. These findings can provide desired decision support for CO2 mitigation of urban agglomeration within a multi-sector and multi-city context. Highlights: A multi-scenario factorial design and multi-regional input-output model is developed. The model is used for analyzing CO2 emission system. The CO2 emission in Jing-Jin-Ji region is evaluated. The effects of different emission mitigation strategies are simulated. Decision support to CO2 mitigation policies can be provided.